What's driving energy efficient appliance label awareness and purchase propensity? - Bradford F. Mills; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
The EU appliance energy consumption labeling scheme is a key component of efforts to increase the diffusion of energy-efficient household appliances. In this paper, the determinants of consumer knowledge of the energy label for house-hold appliances and the choice of class-A energy-efficient appliances are jointly estimated using data from a large survey of more than 20,000 German house-holds. The results for five major appliances suggest that lack of knowledge of the energy label can generate considerable bias in both estimates of rates of uptake of class-A appliances and in estimates of the underlying determinants of choice of class-A appliance. Simulations of the choice to purchase a class-A appliance, given knowledge of the labeling framework, reveal that residence characteristics and, in several cases, regional electricity prices strongly increase the propensity to purchase a class-A appliance, but socio-economic characteristics have surprisingly little impact on appliance energy-class choice.
urn:nbn:de:0011-n-907333
Keywords: 330; Umweltzeichen; Energiesparen; Wahrnehmung; Konsumentenverhalten; Informationsverhalten; Elektrohaushaltsgerät; Deutschland